Preparation, characterization, and water-sorption study of polyvinyl alcohol based hydrogels with grafted hydrophilic and hydrophobic segments - Shukla, S.; Bajpai, A. K.; Kulkarni, R. A. (Journal of Applied Polymer Science, 2005)
The interpenetrating polymer network hydrogels based on poly(vinyl alcohol) were obtained by graft copolymerization of acrylamide and styrene onto polyvinyl alcohol in the presence of N,N'-methylene bisacrylamide as a crosslinking agent. The hydrogels were characterized by optical microscopy, scanning electron microscopy, infrared spectral analysis, differential scanning calorimeter, and thermogravimetric analysis. The hydrogels showed enormous swelling in aqueous medium and displayed swelling characteristics, which were highly dependent on the chemical composition of the hydrogels and pH of the swelling medium. The kinetics of water uptake and the mechanisms of water transport were studied as a function of composition of the hydrogel and pH of the swelling medium. (C) 2005 Wiley Periodicals, Inc.
Keywords: Characterization; equilibrium swelling; grafting; IPN hydrogels; polyvinyl alcohol

Self assembled hydrophobic nanoclusters of poly(methylmethcrylate) embedded into polyvinyl alcohol based hydrophilic matrix: preparation and water sorption study - Shukla, Sandeep Kumar; Shaikh, A. Wasif; Gunari, Nikhil; Bajpai, A. K.; Kulkarni, R. A. (Journal of Applied Polymer Science, 2009)
Hydrophilic matrices containing nanosized Clusters of hydrophilic moieties have demonstrated potential applications in biomedical field. A novel hydrogel containing nanosized domains (20-35 nm) of hydrophobic moieties of poly(methyl methacrylate) (PMMA) was prepared by grafting crosslinked p ly(acrylic acid-co-methyl-methacrylate) chains onto polyvinyl alcohol (PVA) backbone using an efficient redox system. The graft copolymerization process was investigated to observe the influence of gel components on the kinetic parameters of grafting such as rate of grafting (R(g)), grafting yield (G(y)) and grafting efficiency (G(e)). The prepared graft nanohydrogel was evaluated for its water sorption potential under varying chemical composition of the gel and changing pH, temperature, and ionic strength of the swelling bath. The swelling process was also examined mechanistically and diffusion constants (D) of water molecules through the swellable nanohydrogel were also evaluated. (c) 2008 Wiley Periodicals, Inc. J ppl Polym Sci 111: 1300-1310, 2009
Keywords: graft copolymers; hydrophilic polymers; Nanocomposites; swelling